Reaper Follows - Graham, Heather (Toronto, Ontario, Canada Mira, 2024)
Agents from the FBI and Florida Department of Law Enforcement investigate a series of murders linked to conspiracy theorists and doomsday cults.
113553
Keywords: United States -- Federal Bureau of Investigation -- Officials and employees -- Fiction; Policewomen -- Fiction; Serial murder investigation -- Fiction; Conspiracy theories -- Fiction; Government investigators -- Florida -- Fiction; Man-woman relationships -- Fiction; Homicide -- Fiction; Everglades (Fla.) -- Fiction; Florida -- Fiction; Romantic suspense fiction; Detective and mystery fiction; Thrillers (Fiction); Novels